Hemorrhagic shock due to branch injury of the left internal thoracic artery two days after pericardiocentesis. Issue 1 (July 2018) - Hijikata, Sadahiro; Miyamoto, Takamichi; Yamaguchi, Tetsuo; Yamaguchi, Junji; Iwai, Takamasa; Watanabe, Keita; Sagawa, Yuichiro; Masuda, Ryo; Miyazaki, Ryoichi; Miwa, Naoyuki; Hara, Nobuhiro; Nagata, Yasutoshi; et al.
Abstract: Pericardiocentesis is a definitive strategy to remove pericardial effusion. In this report, we present a rare case of a 23-year-old man with sudden delayed hemorrhagic shock due to branch bleeding of the left internal thoracic artery (LITA) two days after undergoing pericardiocentesis. Angiography, embolization, and drainage were effective. As far as we know, this is the first report that shows delayed bleeding due to branch injury of the LITA as a possible complication after pericardiocentesis. <Learning objective: Pericardiocentesis using an apical approach under echocardiography is considered safe; however, in this case, unexpected complications after pericardiocentesis for hemorrhagic shock occurred. Patients who undergo pericardiocentesis should be observed in the hospital for several days. If sudden changes in vital signs occur, the underlying complications should also be considered, and it is important to act promptly and review the patient's prior procedures.>